Management of Zakat, Infak and Alms (Zis) Funds in Improving the Welfare of Mustahik (Study of the Laz Sidogiri Program, Pasuruan, East Java) - A Jamali; Abdul Wahid Al-Faizin; Muhyiddin Muhyiddin (Journal Markcount Finance, 2025)
This study aims to analyze the management of Zakat, Infaq, and Alms (ZIS) funds by the Sidogiri Zakat Collection Institution (LAZ) in improving the welfare of those entitled to receive Zakat (mustahik) in Pasuruan, East Java. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation studies. The results indicate that LAZ Sidogiri has implemented an integrated ZIS management system through various flagship programs such as productive economic programs, education, health, and da'wah (Islamic outreach). The ZIS distribution system is implemented through a consumptive and productive approach with a transparent and accountable distribution mechanism. However, obstacles remain in terms of limited human resources, technological infrastructure, and coordination between programs. Possible optimization strategies include developing an integrated information system, increasing human resource capacity, diversifying programs, and strengthening strategic partnerships. This research contributes to the development of an effective ZIS management model to improve the welfare of those entitled to receive Zakat (mustahik) in Indonesia